A Phase II and Pharmacodynamic Trial of RO4929097 for Patients With Recurrent/Progressive Glioblastoma. Issue 2 (7th October 2020) - Peereboom, David M; Ye, Xiaobu; Mikkelsen, Tom; Lesser, Glenn J; Lieberman, Frank S; Robins, H Ian; Ahluwalia, Manmeet S; Sloan, Andrew E; Grossman, Stuart A
Abstract: BACKGROUND: Cancer stem-like cells are a major cause of resistance to therapy in patients with glioblastoma (GBM) as well as other cancers. Tumor cells are maintained in a stem-like proliferative state in large part through the Notch signaling pathway. The function of this pathway in turn depends on gamma secretase activity. Inhibition of this enzyme therefore inhibits the Notch pathway and tumor growth as measured by a reduction in the formation of brain tumor neurospheres in murine models. RO4929097 is an oral gamma secretase inhibitor. OBJECTIVE: To estimate the 6-mo progression-free survival rate (PFS6 ) in patients with progressive GBM and to inhibit by 50% the generation of neurospheres in fresh tissue resected from patients treated with RO4929097. METHODS: In this phase II and pharmacodynamic study, patients with recurrent GBM received RO4929097 in a study of 2 groups. Group A patients had unresectable disease and received drug in a standard phase II design. Group B patients had resectable disease and received drug before and after surgical resection. Endpoints included PFS6 and the inhibition of neurosphere formation in the resected tumor samples. RESULTS: A total of 47 patients received treatment, 7 of whom had tumor resection. The PFS6 was 4%, and the inhibition of neurosphere formation occurred in 1 of 7 patient samples. CONCLUSION: RO4929097 was inactive in recurrent GBM patients and demonstrated minimal inhibition of neurosphere formation in fresh tissue samples. Graphical Abstract: